Kebijakan Kepala MTs NW Samawa Dalam Menyikapi Problematika Pendidikan Islam di Sumbawa - Adet Tamula Anugrah (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2022)
The problems of Islamic education today are very complex. These problems concern teachers, students, and all people involved in educational institutions. From the many problems faced, it is demanded that there be a solution in the form of policies from the head of madrasah in order to maintain the existence and quality of Islamic educational institutions. This research aims to understand how the formulation, implementation, and policy barriers made by the head of MTs NW Samawa in addressing the challenges and problems faced by Islamic education. This research is a qualitative research with data collection through interviews, observation, and documentation. The results of this study revealed that the birth of the policy set by the head of MTs NW Samawa because of the many challenges and problems faced by MTs NW Samawa. The implementation of these policies leads to improving the quality of teachers, education staff, students, guardians of students, and even the general public. Obstacles faced in implementing the policy include a lack of interest in student learning, limited budget to carry out intense training and research for the development of madrasah, and limited time to take a personal approach to provide education to the community.